Assessing muscle fitness changes to resistance training in healthy young adults using the 1-min sit-to-stand test: insights from a mobile app analysis - Alessio Montemurro; Juan D. Ruiz-Cárdenas; Mathieu Gruet; Robin Souron (European Journal of Applied Physiology, 2026)

Muscle endurance, neuromuscular fatigability, and cognitive control during prolonged dual-task in people with chronic obstructive pulmonary disease: a case–control study - Cyril Chatain; Jean-Marc Vallier; Nicolas Paleiron; Fanny Cucchietti Waltz; Sofiane Ramdani; Mathieu Gruet (European Journal of Applied Physiology, 2025)
Purpose Recent studies suggest that, compared to healthy individuals, people with chronic obstructive pulmonary disease (pwCOPD) present a reduced capacity to perform cognitive-motor dual-task (CMDT). However, these studies were focused on short-duration CMDT offering limited insight to prolonged CMDT inducing fatigue, which can be encountered in daily life. The present study aimed to explore the effect of adding a cognitive task during repeated muscle contractions on muscle endurance, neuromuscular fatigability, and cognitive control in pwCOPD compared to healthy participants. Methods Thirteen pwCOPD and thirteen age- and sex-matched healthy participants performed submaximal isometric contractions of the knee extensors until exhaustion in two experimental sessions: (1) without cognitive task and (2) with a concurrent working memory task (i.e., 1-back task). Neuromuscular fatigability (as well as central and peripheral components measured by peripheral magnetic stimulation), cognitive performance, and perceived muscle fatigue were assessed throughout the fatiguing tasks. Results Independently to the experimental condition, pwCOPD exhibited lower muscle endurance compared to healthy participants ( p = 0.039), mainly explained by earlier peripheral fatigue and faster attainment of higher perceived muscle fatigue ( p < 0.05). However, neither effect of cognitive task ( p = 0.223) nor interaction effect (group × condition; p = 0.136) was revealed for muscle endurance. Interestingly, cognitive control was significantly reduced only in pwCOPD at the end of CMDT ( p < 0.015), suggesting greater difficulty for patients with dual tasking under fatigue. Conclusion These findings provide novel insights into how and why fatigue develops in COPD in dual-task context, offering a rationale for including such tasks in rehabilitation programs.

The 1-min sit-to-stand test induces a significant and reliable level of neuromuscular fatigability: insights from a mobile app analysis - Robin Souron; Juan D. Ruiz-Cárdenas; Mathieu Gruet (European Journal of Applied Physiology, 2024)

Enhancing endurance performance with combined imagined and actual physical practice - Robin Souron; Benjamin Pageaux; Nathan Grosboillot; Aymeric Guillot; Mathieu Gruet; Mathilde F. Bertrand; Guillaume Y. Millet; Thomas Lapole (European Journal of Applied Physiology, 2024)

The time course of different neuromuscular adaptations to short-term downhill running training and their specific relationships with strength gains - Bastien Bontemps; Mathieu Gruet; Julien Louis; Daniel J. Owens; Stella Miríc; Robert M. Erskine; Fabrice Vercruyssen (European Journal of Applied Physiology, 2022)
Purpose Due to its eccentric nature, downhill running (DR) training has been suggested to promote strength gains through neuromuscular adaptations. However, it is unknown whether short-term chronic DR can elicit such adaptations. Methods Twelve untrained, young, healthy adults (5 women, 7 men) took part in 4 weeks’ DR, comprising 10 sessions, with running speed equivalent to 60–65% maximal oxygen uptake ( $$\dot{V}$$ V ˙ O 2max , assessed at weeks 0 and 4). Isometric and isokinetic knee-extensor maximal voluntary torque (MVT), vastus lateralis (VL) muscle morphology/architecture (anatomical cross-sectional area, ACSA; physiological CSA, PCSA; volume; fascicle length, L f ; pennation angle, PA) and neuromuscular activation (VL EMG) were assessed at weeks 0, 2 and 4. Results MVT increased by 9.7–15.2% after 4 weeks ( p < 0.01). VL EMG during isometric MVT increased by 35.6 ± 46.1% after 4 weeks ( p < 0.05) and correlated with changes in isometric MVT after 2 weeks ( r = 0.86, p = 0.001). VL ACSA (+2.9 ± 2.7% and +7.1 ± 3.5%) and volume (+2.5 ± 2.5% and +6.6 ± 3.2%) increased after 2 and 4 weeks, respectively ( p < 0.05). PCSA (+3.8 ± 3.3%), PA (+5.8 ± 3.8%) and L f (+2.7 ± 2.2%) increased after 4 weeks ( p < 0.01). Changes in VL volume ( r = 0.67, p = 0.03) and PCSA ( r = 0.71, p = 0.01) correlated with changes in concentric MVT from 2 to 4 weeks. $$\dot{V}$$ V ˙ O 2max (49.4 ± 6.2 vs. 49.7 ± 6.3 mL·kg −1 ·min −1 ) did not change after 4 weeks ( p = 0.73). Conclusion Just 4 weeks’ moderate-intensity DR promoted neuromuscular adaptations in young, healthy adults, typically observed after high-intensity eccentric resistance training. Neural adaptations appeared to contribute to most of the strength gains at 2 and 4 weeks, while muscle hypertrophy seemed to contribute to MVT changes from 2 to 4 weeks only.

Overall and differentiated sensory responses to cardiopulmonary exercise test in patients with cystic fibrosis: kinetics and ability to predict peak oxygen uptake - Mathieu Gruet; Laurent Mely; Jean-Marc Vallier (European Journal of Applied Physiology, 2018)

Population Pharmacokinetic Analysis of Blood and Joint Synovial Fluid Concentrations of Robenacoxib from Healthy Dogs and Dogs with Osteoarthritis - Hanna E. Silber; Claudia Burgener; Ingrid M. Letellier; Mathieu Peyrou; Martin Jung; Jonathan N. King; Philippe Gruet; Jerome M. Giraudel (Pharmaceutical Research, 2010)